2021
DOI: 10.3390/su13063164
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Practices in Hospitality: Case Study of a Luxury Hotel in Arrábida Natural Park

Abstract: The agenda of researchers and practitioners in the tourism industry has focused on the demand for sustainable practices. Luxury hotels have also followed this trend, although studies are still limited. The aim of this study is to understand what environmental and social sustainability practices luxury hotels are adopting and how their management perceive the benefits and results from their adoption. This empirical research is based on a case study that triangulates data from semi-structured interviews, documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 69 publications
(141 reference statements)
2
84
0
3
Order By: Relevance
“…From a corporate strategy point of view, these practices are more associated with cost reduction and efficiency than product differentiation. Based on the case study by Pereira et al [52], the cost reduction may be as high as 40%. As mentioned, Kularatne et al [35] also found efficiency gains resulting from sustainable practices, although with contradictory results concerning gains from reduced water consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a corporate strategy point of view, these practices are more associated with cost reduction and efficiency than product differentiation. Based on the case study by Pereira et al [52], the cost reduction may be as high as 40%. As mentioned, Kularatne et al [35] also found efficiency gains resulting from sustainable practices, although with contradictory results concerning gains from reduced water consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, some authors, such as Chandran and Bhattacharya [67] and Saura et al [71], found that green marketing may enhance reputation. Han et al [72] found that green marketing can also increase consumer loyalty, whereas Pereira et al [52] argue that it is possible to achieve compatibility between luxury and environmental sustainability practices in the hospitality context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-being in the workplace is "the overall quality of an employee's experience and functioning at work" (Grant et al, 2007, p. 52). Promoting employee well-being through training and development opportunities and favourable working conditions is not only a corporate responsibility but also a contribution to social sustainability (Modica et al, 2020;Pereira et al, 2021). However, the well-being of (non)managerial personnel is concerning because of workplace bullying behaviour expressed in verbal abuse, inappropriate jokes, sexual harassment and mean pranks.…”
Section: Local Food Usementioning
confidence: 99%
“…The hotel industry represents an essential part of the tourism industry and, consequently, on the one hand, pollutes the environment, while on the other hand, due to its part in the tourism industry, it has many opportunities to contribute significantly to lowering its negative impacts on the environment, such as global warming and depletion of natural resources [1]. Higher environmental awareness, the intersection between business and environmental issues [2] and some other changes, such as digitalisation in the last twenty years, have shown that there is a need for the improvement of effectiveness and efficacy of hotels [3]. Environmental protection and addressing key environmental issues are becoming increasingly important factors in the hotel business and influence hoteliers' competitiveness in the market, whereby the key issue is their ability to manage environmental performance and establish efficiency in that process.…”
Section: Introductionmentioning
confidence: 99%